Performance and Knowledge of Rural Women in Banda District About Kitchen Gardening After Training and Demonstration (Indian Journal of Extension Education, 2019)
The present investigation was carried out by Krishi Vigyan Kendra, Banda, Uttar Pradesh. The aim of the study was to assess the extent of knowledge gained and changes in production of vegetables due to the intervention of establishment of model Kitchen garden, accompanied trainings (on campus as well as off campus) and demonstrations by selected farming families of Banda district. Total 50 rural women were randomly selected for the study. Kitchen garden Kit developed by Indian Institute of Vegetable Research, Varanasi was also supplied as critical input among rural women for nutritional farming. The study highlighted that after the training and demonstration on model kitchen garden, there was a significant increase in production of vegetables i.e. 145.12 percent. 47.6 percent changes in knowledge was observed and family size, land holding, experience and training were found significantly correlated with gain in knowledge. It can be concluded that Kitchen gardening has proved a feasible livelihood strategy for rural people in terms of nutrient as well as calorie intake and economic performances.